Intercultural Relations in Plural Societies: Implications for Living Together in Vietnam - W. Berry, John (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
There is probably no more serious challenge to social stability and cohesion in the contemporary world than the management of intercultural relations within culturally plural societies.  Successful management depends on many factors including a research-based understanding of the historical, political, economic, religious and psychological features of the groups that are in contact. The core question is “How shall we all live together?”  In the project reported in this paper, we seek to provide such research by examining three core psychological hypotheses of intercultural relations (multiculturalism, contact and integration) in 17 culturally plural societies. The main goal of the project is to evaluate these three hypotheses across societies in order to identify some basic psychological principles that may underlie intercultural relations. The eventual goal is to employ the findings to propose some policies and programmes that may improve the quality of intercultural relationship globally. The empirical findings in these 17 societies generally support the validity of the three hypotheses. Implications for the development of policies and programmes to enhance the quality of intercultural relations are discussed.Received 30 March 2018; Revised 20 April 2018; Accepted 28 April 2018